Assessment of area at risk of flood and drought in the SeThamok Sub-basin: https://doi.org/10.69692/SUJMRD1001183 - Anothai , Sakounxay; Xaypanya, Phetyasone; Chanthavongsa, KhamKeng; Kimmany , Bounhome; Phetaoi, Khamlar (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The problem of floods and drought is a serious problem and has affected many areas in many areas of the world including Lao PDR. SeThaMok sub-basin is a sub-basin that suffers from disasters as mentioned almost every year, especially in Phin district, which has caused enormous damage. Because of such a problem, it is necessary to assess the risk areas for floods and droughts in order to manage floods and droughts that are suitable for the area in order to move forward in planning to deal with floods and droughts in the future. Therefore, this study aims to study flood and drought risk areas as well as create flood maps in (2014, 2018, 2019) and drought maps in (2006, 2012, 2015) using ArcGIS 10.5. This study uses rainfall data from 4 stations using the Thiessen Polygon Method to calculate the average rainfall and using data from the survey, collecting actual data from the field together with the data collected by the Department of Natural Resources and Environment. The results of the study found that: in 2014, there was a flood area covering 11.93% of the total catchment area and the maximum flood level was about 26 meters compared to the lowest level of the catchment area. Among them, the flood event covered 20 villages; In 2018, there is a flood area covering 16.06% of the total catchment area and the maximum flood level is about 32 meters. Among them, the flood event covered 27 villages; In 2019, there is a flood area covering 20.91% and the maximum flood level is about 34 meters. Among them, the flood event covered 39 villages and the results of the evaluation of areas at risk of drought showed that: in 2007, there were areas at risk of drought covering 39.18% of the area of the SeThaMok sub-watershed which covered the number of villages around 32 villages; In 2012, there is a drought-prone area covering 43.29% of the SeThaMok sub-watershed area, which covers about 38 villages; In 2015, there is a drought-prone area covering 36.73% of the SeThaMok sub-basin area, which covers about 30 villages.